A Web-based Village Administrative Information Systems fo Improvement Quality of Service towards Smart Village Concept - Kenrick Filbert Siman; Jansen Wiratama (G-Tech: Jurnal Teknologi Terapan, 2023)
Public services are things that the government must provide to its citizens. The availability of technological devices that support village services is available. It can be used, but in realizing its activities so far, many villages still need to be more optimal in providing services because they still need to use conventional methods. This research was conducted in Cihuni Village, located in Banten Province, with an area of ± 571.20ha. As of 2020, Cihuni Village is known to have a population of 7,111 people. With such a large population, conventional service methods cannot run optimally. Therefore, an information system is needed to assist village officials in managing the administration of their residents. The Village Administration Information System was designed using the System Development Life Cycle (SDLC) method using the Rapid Application Development (RAD) model. The process carried out in this study begins with the Requirements Planning, User Design, Construction, and Cut Over stages according to the RAD model. At the design stage, the Bootstrap Framework is used as the front end, and the Laravel Framework is used as the back end for the web-based Village Administration Information System. The results of testing with test cases using the User Acceptance Test (UAT) method obtained results that were following the needs of Cihuni village.